Direct interaction of avermectin with epidermal growth factor receptor mediates the penetration resistance in Drosophila larvae. Issue 4 (April 2016) - Chen, Li-Ping; Wang, Pan; Sun, Ying-Jian; Wu, Yi-Jun
Abstract : With the widespread use of avermectins (AVMs) for managing parasitic and agricultural pests, the resistance of worms and insects to AVMs has emerged as a serious threat to human health and agriculture worldwide. The reduced penetration of AVMs is one of the main reasons for the development of the resistance to the chemicals. However, the detailed molecular mechanisms remain elusive. Here, we use the larvae of Drosophila melanogaster as the model organism to explore the molecular mechanisms underlying the development of penetration resistance to AVMs. We clearly show that the chitin layer is thickened and the efflux transporter P-glycoprotein (P-gp) is overexpressed in the AVM-resistant larvae epidermis. We reveal that the activation of the transcription factor Relish by the over-activated epidermal growth factor receptor (EGFR)/AKT/ERK pathway induces the overexpression of the chitin synthases DmeCHS1/2 and P-gp in the resistant larvae. Interestingly, we discover for the first time, to the best of our knowledge, that AVM directly interacts with EGFR and leads to the activation of the EGFR/AKT/ERK pathway, which activates the transcription factor Relish and induces the overexpression of DmeCHS1/2 and P-gp. These findings provide new insights into the molecular mechanisms underlying the development of penetration resistance to drugs.